The Treaty on the Functioning of the European Union as a supplementary source of law in the Andean Community. Free trade and state sovereignty - Reyes Tagle, Yovana (2024)
The Andean Court of Justice (ACJ) considered Article 34 Treaty on the Functioning of the European Union (TFEU) as a supplementary source of law to interpret the principle of free movement of goods in the Andean Community (CAN). The Cartagena Agreement does not provide for the concept of measure of equivalent effect to quantitative restrictions. The objective of this article is to analyze the implications of employing the TFEU as a supplementary source of law and the regulatory capacity of the Member States of the CAN. It is argued that considering the TFEU as a supplementary source of law to interpret the principle of free movement of goods in the CAN facilitated the extensive interpretation of the Cartagena Agreement with the risk of reducing state regulatory capacity.